Indebtedness and spending: What happens when the music stops? - Julia Le Blanc; Reamonn Lydon (European Central Bank (ECB), 2020)
We analyse the effect of shocks to housing wealth and income before and after the Great Recession. We combine datasets containing information on expenditure, income, wealth and debt in a synthetic panel to understand how household indebtedness affects the response to income and wealth shocks.We find evidence for both a housing wealth effect and income shocks depressing household consumption during the crisis in Ireland. The long recovery of consumption is also related to high levels of indebtedness at the onset of the crisis. Households who entered the crisis with more debt are significantly more sensitive to changes in their income. In this way, household balance sheets can be an important amplification mechanism for aggregate shocks.
Keywords: D14; D31; E21; H31; 330; Housing; income; wealth; expenditure